Triple Therapy with Scopolamine, Ondansetron, and Dexamethasone for Prevention of Postoperative Nausea and Vomiting in Moderate to High-Risk Patients Undergoing Craniotomy Under General Anesthesia: A Pilot Study - Bergese, Sergio D.; Antor, Maria A.; Uribe, Alberto A.; Yildiz, Vedat; Werner, Joseph (Frontiers in Medicine, 2015)
Introduction: Postoperative nausea and vomiting is one of the most common complaints from patients and clinicians after a surgical procedure. According to the current Society of Ambulatory Anesthesia Consensus Guidelines, the general incidence of vomiting and nausea is around 30% and 50% respectively; and up to 80% in high risk patients. In previous studies, the reported incidence of PONV at 24 hours after craniotomy was 43%-70%. The transdermal scopolamine delivery system contains a 1.5 mg drug reservoir, which is designed to deliver a continuous slow release of scopolamine through intact skin during the first 72 hours of patch application. Therefore, we designed this single arm, non-randomized, pilot study to assess the efficacy and safety of triple therapy with scopolamine, ondansetron and dexamethasone to prevent PONV. Materials and methods: In the preoperative area, subjects received an active TDS 1.5 mg that was applied to a hairless patch of skin in the mastoid area approximately 2 hours prior to the operation. Immediately after anesthesia induction, all patients received a single 4 mg dose of ondansetron IV and a single 10 mg dose of dexamethasone IV. Patients that experienced nausea and/or vomiting received ondansetron 4 mg IV as the initial rescue medication. Results: A total of 36 subjects were analyzed. The overall incidence of PONV during the first 24 hours after neurological surgery was 33% (n=12). The incidence of nausea and emesis during the first 24 hours after surgery was recorded as 33% (n=12) and 16% (n=6) respectively. Conclusion: Our data also showed that this triple therapy regimen may be an efficient alternative regimen for PONV prophylaxis in patients undergoing neurological surgery with general anesthesia. Further studies using regimens affecting different receptor pathways should be performed to better prove the efficacy in preventing PONV or delayed PONV.